5w+1=3w-3

Simple and best practice solution for 5w+1=3w-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w+1=3w-3 equation:


Simplifying
5w + 1 = 3w + -3

Reorder the terms:
1 + 5w = 3w + -3

Reorder the terms:
1 + 5w = -3 + 3w

Solving
1 + 5w = -3 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
1 + 5w + -3w = -3 + 3w + -3w

Combine like terms: 5w + -3w = 2w
1 + 2w = -3 + 3w + -3w

Combine like terms: 3w + -3w = 0
1 + 2w = -3 + 0
1 + 2w = -3

Add '-1' to each side of the equation.
1 + -1 + 2w = -3 + -1

Combine like terms: 1 + -1 = 0
0 + 2w = -3 + -1
2w = -3 + -1

Combine like terms: -3 + -1 = -4
2w = -4

Divide each side by '2'.
w = -2

Simplifying
w = -2

See similar equations:

| m(x)=-6.5x | | 5b+1=2(b+2) | | x-48=28-3x | | 5x+5+5=14+2x | | h(x)=2.25x | | 37x+12y=22 | | (.5)(6)(x)=27 | | -35-7x=23-9x | | -95+2x=118-6x | | 3+5+x=10 | | -95+2x=-9x+37 | | 5x-3=6x+14x | | a-3=5-s | | 47q-2=61q-86 | | 9k=-300 | | -28-5x=22-7x | | -4x+8+6x=2 | | x-(4x-12)=18 | | z^10-2*z^5+2=0 | | (6x-5)(6x-7)=0 | | x=loge^2 | | 12y-12x-(-13y-65x)= | | 4100=4000n-500 | | -113+5x=118-6x | | 12-m=5m-6 | | 5.6=2.3+3z | | 0=-16x^2+24x+160 | | 2.5x+.45=.95 | | ab-5ab+15ab= | | 18+4m=50 | | x^2+12x=37x+150 | | 1470+7(s-30)=4300 |

Equations solver categories